2014
DOI: 10.9738/intsurg-d-14-00090.1
|View full text |Cite
|
Sign up to set email alerts
|

Production of Intraperitoneal Interleukin-6 Following Open or Laparoscopic Assisted Distal Gastrectomy

Abstract: The interleukin (IL)-6 concentration in plasma or serum has been considered to represent the degree of stress resulting from surgery. However, IL-6 in peritoneal fluid has rarely been considered. The aim of this study was to assess the concentration and amount of IL-6 in peritoneal fluid as indicators of surgical stress. To obtain basic data on peritoneal release of IL-6 during gastric cancer surgery, we measured IL-6 in peritoneal drainage samples, stored for up to 72 hours postoperatively, from patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…However, IL-6 growth during open cholecystectomy was greater compared to laparoscopic cholecystectomy (62.51-fold vs. 3.19-fold). Our results are in line with other studies indicating increased inflammatory response in open surgery in comparison to the equivalent laparoscopic one [ 19 22 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, IL-6 growth during open cholecystectomy was greater compared to laparoscopic cholecystectomy (62.51-fold vs. 3.19-fold). Our results are in line with other studies indicating increased inflammatory response in open surgery in comparison to the equivalent laparoscopic one [ 19 22 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with findings of Shietroma et al [ 43 , 44 ], who observed that blood IL-6 concentration began to significantly increase as early as 1 hour from the beginning of the operation. Current results also confirmed the concept, presented by other authors [ 19 , 36 , 38 , 42 ], that IL-6 concentration is very strongly and positively correlated with the hospital stay after surgery.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…IL-1β and IL-2 are the inflammatory factors mediating inflammatory reaction, which have a direct effect on target tissue and cause inflammatory injury [13]. IL-6 is a multifunctional cytokine which has a regulation effect on inflammatory reaction and immune reponse, and it can also mediate the cascade amplification of inflammatory reaction [14]. IL-8 is the cytokine with an effect of neutrophils chemotaxis, which can improve the activation of neutrophile granulocyte and the release of elastinase during the process of inflammatory reaction [15].…”
Section: Discussionmentioning
confidence: 99%